HUBUNGAN ANTARA PENGGUNAAN AIR BERSIH DAN TINDAKAN PENCEGAHAN DIARE DENGAN DIARE PADA BALITA DI KELURAHAN KEBON BAWANG TANJUNG PRIOK - Nurdin, Gusti (Jurnal Matematika Sains dan Teknologi, 2004)
This research was made for knowing if there’s of the use of relation between The Use of Fresh Water and The Prevention of Diare Treatment Disease With Diare of babies and children (Balita) in sub district Kebon Bawang of Tanjung Priok. This research use descriptive method and correlation approach conducted of many mothers in sub district of Tanjung Priok Jakarta Utara with 13.687 people of research population 162 samples of people or 1,2 % of population taken with purposive random sampling technique. The results of the first hypothesis showed that there is a positive relation and significant between The Use of Fresh Water with Diare on babies and children in sub district of Tanjung Priok with truth of examination. The result of the second hypothesis showed there is a positive relation and significant between The Prevention of Diare Treatment Disease with Diare on babies and children (Balita) in sub district of Tanjung Priok with truth of examination. The result of third hypothesis showed that there is a positive relation and significant between The Use of Fresh Water and The Prevention of Diare Treatment Disease with Diare a long with the babies and children (Balita) in sub district of Tanjung Priok with the truth of examination. The conclusion of this research is the positive relation and significant between The Use of Fresh Water with Diare of babies and children (Balita), between The Prevention of Diare Treatment Disease and between The Use of Fresh Water and The Prevention of Diare Treatment Disease with Diare a long with the babies and children (Balita) in sub district of Tanjung Priok North Jakarta.